Alternatives for End-of-Life Tire Disposal - Bueno, Luana Maria Moreira Godoy; Teles, Renan Meira; Prates, Kátia Valéria Marques Cardoso (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This research addresses the topic of proper disposal of end-of-life tires, which are composed of rubber, carbon black, textiles, and steel. The problem with end-of-life tires is directly linked to their non-biodegradability, as these residues can take up to six centuries to decompose. Numerous environmental, public health, and economic issues arise from the improper accumulation of this waste. Therefore, this study focuses on a systematic literature review aimed at identifying various environmentally appropriate disposal methods for end-of-life tires in Brazil and worldwide, categorizing them into reuse, recovery, and recycling. It also examines how end-of-life tires are collected in Brazil to understand the main challenges in transporting this waste to facilities capable of proper disposal. End-of-life tires have the potential to be transformed into raw materials for crafting, incorporated into construction materials, or even used as an alternative fuel source in the cement industry. Thus, the proper disposal of end-of-life tires is crucial for preserving natural resources and reducing waste accumulation, preventing environmental damage and harm to public health. In most cases, end-of-life tires are reused or recycled, and in fewer cases, recovered.